2023
DOI: 10.1002/dev.22378
|View full text |Cite
|
Sign up to set email alerts
|

A review of the literature: How does prenatal opioid exposure impact placental health and fetal brain development?

Abstract: In recent years, there has been a sixfold increase in the number of pregnant people with opioid use disorder (OUD). Rates of neonatal opioid withdrawal syndrome (NOWS), previously known as neonatal abstinence syndrome (NAS), have significantly increased in virtually every state and demographic group (Healthcare Cost Utilization Project, HCUP, 2010). NOWS is a condition resulting from chronic exposure to either therapeutic opioid use (e.g., medication for OUD, chronic pain conditions) or nonprescribed opioid us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
(95 reference statements)
1
4
0
Order By: Relevance
“…We observed relatively large placentas despite maternal smoking, which is typically associated with small placentas and birth sizes. These large size of the placentas was linked to maternal methadone treatment, concomitant substance use, and hepatitis C, which is in line with previous research 23–25 …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We observed relatively large placentas despite maternal smoking, which is typically associated with small placentas and birth sizes. These large size of the placentas was linked to maternal methadone treatment, concomitant substance use, and hepatitis C, which is in line with previous research 23–25 …”
Section: Discussionsupporting
confidence: 90%
“…Placental size and function also impact foetal growth and health 22,23 . We observed relatively large placentas despite maternal smoking, which is typically associated with small placentas and birth sizes.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The long‐term epigenetic effects on proteins, receptors and neurotransmitters important for cognition result in impaired learning and memory 6 . Chronic opioid exposure has also been shown to be harmful to placental function 7 . Adding to this, magnetic resonance imaging studies have reported reduced basal ganglia volumes and white matter microstructure alterations in opioid‐exposed infants and older children 8,9 …”
Section: Introductionmentioning
confidence: 99%
“…6 Chronic opioid exposure has also been shown to be harmful to placental function. 7 Adding to this, magnetic resonance imaging studies have reported reduced basal ganglia volumes and white matter microstructure alterations in opioid-exposed infants and older children. 8,9 The most undesirable neonatal outcome associated with prenatal OMT exposure in humans is Neonatal Abstinence Syndrome, with an incidence rate of 40-90%.…”
mentioning
confidence: 98%